IEEE INFOCOM 2003. Twenty-Second Annual Joint Conference of the IEEE Computer and Communications Societies (IEEE Cat. No.03CH37 2003
DOI: 10.1109/infcom.2003.1208943
|View full text |Cite
|
Sign up to set email alerts
|

Packets distribution algorithms for sensor networks

Abstract: Abstract-In this paper, we study, via simple discrete mathematical models, the problems of data distribution and data collection in wireless sensor networks. The work that follows continues the work presented by the authors in [1] where the focus was on sensor networks equipped with unidirectional antenna elements. Here we shift our interest to networks equipped with omnidirectional antenna elements. In particular we show how the data distribution and collection tasks can be performed optimally (with respect t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
71
0

Year Published

2005
2005
2021
2021

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 63 publications
(73 citation statements)
references
References 12 publications
0
71
0
Order By: Relevance
“…Phase 1. Node s collects all messages by modifying a data dissemination algorithm by Florens and McEliece [19]. In the data dissemination problem, a source node sends a different message m(v) to each node v in the network, and they present a 3-approximation algorithm.…”
Section: A Collect-and-distribute Algorithm (Cda)mentioning
confidence: 99%
“…Phase 1. Node s collects all messages by modifying a data dissemination algorithm by Florens and McEliece [19]. In the data dissemination problem, a source node sends a different message m(v) to each node v in the network, and they present a 3-approximation algorithm.…”
Section: A Collect-and-distribute Algorithm (Cda)mentioning
confidence: 99%
“…In [7] it is shown that data distribution and collection tasks can be performed optimally on tree networks. In [8] the performance of a greedy algorithm to build trees in networks of differing densities is evaluated.…”
Section: Related Workmentioning
confidence: 99%
“…The sensors can communicate their decisions to join a particular cluster to its clusterhead according to this schedule without wasting any energy in retransmissions. Once the clusterhead has knowledge of all the sensors in its cluster, it can find a more optimal transmission schedule using strategies proposed in [24,25].…”
Section: Discussionmentioning
confidence: 99%
“…Researchers have also proposed protocols that manage and attempt to minimize the energy spent in gathering data [10,11,16,[23][24][25] in a sensor network. In [23], the authors have proposed schemes that minimize an energy*delay metric in gathering data in sensor networks.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation